PENINGKATAN HASIL BELAJAR SISWA PADA MATERI FAKTORISASI POLINOM MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING - Yandry Niak; Jeinne Mumu; Anderson Leonardo Palinussa (Jurusan Pendidikan MIPA FKIP Universitas Pattimura, 2020)
This study aims to improve student learning outcomes in polynom factorization material using a cooperative learning model type Student Facilitator and Explaining (SFE). This research has qualitative research. The class conducted the action using teaching materials and grup worksheets, which have been adapted to the SFE model and learning is carried out in two cycles. At the end of each cycle a final cycle test is carried out, then the data obtained are analyzed quantitatively and qualitatively. The result of the study showed that there was an increase in the learning outcomes of class XI SMA Negeri 1 Manokwari who were taught to use the SFE type cooperative learning model on polynom factorization material.